Dante en la ficción sentimental. - Zaderenko, Irene (Dicenda. Estudios de lengua y literatura españolas, 1999)
The article examines the possible influence of Dante on the sentimental romance, particularly on the Siervo libre de amor where tbe name of the Italian poet appears. Different aspects of Rodríguez del Padrón's work, in which crities have seen the influence of Dante, are analyzed. The conclusion is that it is improbable that the Italian author had any considerable bearing on the Sie;vo. Instead, the sentimental romance shows the influence of other models present at that time in Castilian literature. Many of the tbemes and metrical forms of the Historia troyana polimétrica, for example, are found in Rodríguez del Padrón's Siervo.
Keywords: Allegory; Dante; Historia troyana; sentimental romance; Siervo libre de amor